Serving up love : [large type] a four-in-one Harvey House brides collection - Peterson, Tracie; Witemeyer, Karen; Jennings, Regina (Regina Lea); Turano, Jen (Thorndike Press large print Christian historical fiction, 2020)
"Bestselling novelist Tracie Peterson joins Karen Witemeyer, Regina Jennings, and Jen Turano in this collection of four novellas, each featuring a Harvey Girl heroine. From Kansas to Texas, the Grand Canyon to New Mexico, the stories cross the country with tales of sweet romance and entertaining history. In Karen Witemeyer's "More Than a Pretty Face," a young woman works her hardest to escape poor choices from her youth. Tracie Peterson offers "A Flood of Love," where reuniting with an old flame after more than a decade offers unexpected results. Regina Jennings's "Intrigue a la Mode" delights with a tale of a young woman determined to help support her family, despite warnings of danger nearby. And Jen Turano's "Grand Encounters" heads to the Grand Canyon with a tale of a society belle intent on finding a new life for herself"--